Comparative effectiveness of dual-focus contact lenses and DIMS spectacle lenses for myopia control in patients with low astigmatism: a retrospective study - Lee, Chia-Yi; Yang, Shun-Fa; Chang, Yu-Ling; Huang, Jing-Yang; Lian, Ie-Bin; Chang, Chao-Kai (Frontiers in Medicine, 2025)
PurposeThis study aimed to evaluate and compare the effectiveness of dual-focus contact lenses (DFCL) and defocus incorporated multiple segment (DIMS) spectacle lenses in controlling myopia progression in patients with low astigmatism.MethodsA retrospective cohort study was conducted involving myopic patients with astigmatism of less than −1.25 diopters (D) who used either DFCL or DIMS spectacle lenses. The study included 95 eyes in the DFCL group and 88 eyes in the DIMS group, and the spherical equivalent refraction (SER) of the study population ranged from −0.50 D to −6.00 D. The primary outcomes were the progression of SER and the elongation of axial length (AXL) over 1 year. A generalized linear mixed model was used to calculate adjusted odds ratios (aORs) and the associated 95% confidence intervals (CIs), adjusting for age, sex, initial AXL, and initial SER.ResultsThe mean SER progression was −0.28 ± 0.15 D in the DFCL group and −0.25 ± 0.12 D in the DIMS group (p = 0.139). The mean AXL elongation was 0.12 ± 0.07 mm for DFCL users and 0.10 ± 0.05 mm for DIMS users (p = 0.029). Trend analysis revealed no significant differences in SER progression (aOR: 0.988; 95% CI: 0.945–1.033; p = 0.513) or AXL elongation (aOR: 0.982; 95% CI: 0.945–1.018; p = 0.307) between the groups after adjusting for confounders. Subgroup analyses indicated no significant differences in SER progression or AXL elongation between DIMS and DFCL users across different baseline characteristics (all p > 0.05).ConclusionThe use of DIMS spectacle lenses showed SER and AXL control similar to that of DFCL.